NAT10 promotes osteoclastogenesis in inflammatory bone loss by catalyzing Fos mRNA ac4C modification and upregulating MAPK signaling pathway - Ruhan Yang; Weijun Yu; Lu Lin; Zhurong Cui; Jiaqi Tang; Guanglong Li; Min Jin; Yuting Gu; Eryi Lu (Journal of Advanced Research)
Introduction: Excessive osteoclastogenesis is a key driver of inflammatory bone loss. Suppressing osteoclastogenesis has always been considered essential for the treatment of inflammatory bone loss. N-acetyltransferase 10 (NAT10) is the sole enzyme responsible for N4-acetylcytidine (ac4C) modification of mRNA, and is involved in cell development. However, its role in osteoclastogenesis and inflammatory bone loss remained elusive. Objectives: We aimed to clarify the regulatory mechanism of NAT10 and ac4C modification in osteoclastogenesis and inflammatory bone loss. Methods: NAT10 expression and ac4C modification during osteoclastogenesis were determined by quantitative real-time PCR (qPCR), western blotting, dot blot and immunofluorescent staining, and the effect of NAT10 inhibition on osteoclast differentiation in vitro was measured by the tartrate-resistant acid phosphatase staining, podosome belts staining assay and bone resorption pit assay. Then, acRIP-qPCR and NAT10RIP-qPCR, ac4C site prediction, mRNA decay assay and luciferase reporter assay were performed to further study the underlying mechanisms. At last, mice models of inflammatory bone loss were applied to verify the therapeutic effect of NAT10 inhibition in vivo. Results: NAT10 expression was upregulated during osteoclast differentiation and highly expressed in alveolar bone osteoclasts from periodontitis mice. Inhibition of NAT10 notably reduced osteoclast differentiation in vitro, as indicated by great reduction of tartrated resistant acid phosphatse positive multinuclear cells, osteoclast-specific gene expression, F-actin ring formation and bone resorption capacity. Mechanistically, NAT10 catalyzed ac4C modification of Fos (encoding AP-1 component c-Fos) mRNA and maintained its stabilization. Besides, NAT10 promoted MAPK signaling pathway and thereby activated AP-1 (c-Fos/c-Jun) transcription for osteoclastogenesis. Therapeutically, administration of Remodelin, the specific inhibitor of NAT10, remarkably impeded the ligature-induced alveolar bone loss and lipopolysaccharide-induced inflammatory calvarial osteolysis. Conclusions: Our study demonstrated that NAT10-mediated ac4C modification is an important epigenetic regulation of osteoclast differentiation and proposed a promising therapeutic target for inflammatory bone loss.